British or American? Iranian EFL learners’ Perceptions toward English Accents: Exploring possible relationships - Hiwa Weisi; Ali Raygan; Fatemeh Bakhtiari (IJET (Indonesian Journal of English Teaching), 2019)
Native English accents (British and American) are known as highly favored and accepted varieties compared to other existing accents in English as foreign language (EFL) context. Notwithstanding the research accomplished on EFL learners’ attitudes toward either of the accents (British or American), studies are still scant regarding the investigation of their perspectives in detail toward one of the accents specifically within the context of Iran. The aim of this study is to examine the Iranian EFL learners’ attitudes toward the two major known English accents (British and American. Additionally, the study highlights the major factors contributing to the learners’ preferences toward either of the accents (British or American). To that aim, a developed and validated questionnaire was distributed among 108 EFL learners selected from two of the major EFL contexts (universities and private institutes). The results indicated that the majority of the learners preferred American over British English accent. Besides, factor analysis revealed that American English exposure, lack of guidance, and lack of reinforcement toward British accent were among the mentioned factors accepted by learners for their preference of American. Finally, the study concludes with interpretations regarding the learners’ decision making issues in either of the two major accents, and recommendations are provided for revisiting the EFL learners’ attitudes and insights toward native English accents.